Penerapan Sistem Penjaminan Mutu untuk Meningkatkan Kualitas dan Daya Saing Produk Gula Kelapa di Desa Pernasidi - Widya Anggraeni Sanggalangi; Merliana Cahya Amalia; Enjeli Intan Fadila; Anugrah Niken Rahmadani; Nunjilatul Rahmah; Reno Sudarno Putra; Dionysius Alfredo Sinaga; Aiza Yudha Pratama; Miftahol Arifin; Yusup Kurnia (Politeknik Piksi Ganesha Indonesia, 2025)
The coconut sugar industry in Banyumas Regency, particularly in the Gendis Asri Farmer Group in Pernasidi Village, has great potential but faces obstacles in terms of production quality and business management. The main problems include unstable product quality, non-standard production equipment, and weak quality control and logistics management systems. Through the Student Community Empowerment Program (PMM), the concepts of Total Quality Management (TQM), the use of stainless steel equipment, a digital stock recording system, and training in management and digital marketing were implemented. The results showed improvements in efficiency, product quality, and the independence of the farmer group. This program supports the achievement of SDGs 8 and 9 and strengthens the agro-industry-based rural economy.